PENYULUHAN GERAKAN BEBAS STUNTING MELALUI PANGAN SEHAT BERBASIS LOKAL - Dwi Indira, Dyana; Rahmadhan, Fariz Putra; Zahara, Futri Amalia; Khadijah, Siti; Rahmawati, Rafika (An-Nizam, 2025)
Stunting is defined as long-term malnutrition characterized by stunted growth due to poor nutritional intake, frequent infections, and chronic diseases that last from pregnancy to the age of two years. The problem of stunting in Taman Sari Village is very relevant. Field data shows that the prevalence of stunting in this area is around 47 children. Lack of nutritional intake absorbed by the body from the womb to after birth, lack of access to health services, and lack of access to clean water and sanitation are some of the causes of stunting. The purpose of this study is to increase public awareness of the importance of balanced nutrition and prevent stunting early on. The method used in this study is the method of socialization to the community, especially parents in Taman Sari Village. The results of this study indicate that the counseling went well and provided new information needed by the community. This counseling provides a good understanding and can be directly applied in everyday life.